Cross-Cultural Adaptation and Validation of RANAS-Based Instrument for Measuring Latrine Use Behavior in Indonesia - Yulyani, Vera; Dewi, Fatwa Sari Tetra; Iswanto, Iswanto (UI Scholars Hub, 2025)
Using toilets is a simple way to prevent diarrhea, yet no validated tool exists to measure this habit. This study aimed to develop and validate instruments for measuring latrine use consistency. This questionnaire was adapted from the risk, attitude, norm, ability, and self-regulation (RANAS) framework developed in India and modified for Indonesia. It was evaluated by three experts using the content validity index (CVI). The face validity index (FVI) was pilot-tested on 40 community respondents. Variables measured included behavior, habits, intentions to use toilets, knowledge, attitudes, norms, abilities, and self-regulation. Question items with relevance and clarity scores of item CVI above 0.80 were considered valid and appropriate. Item scoring 0.70–0.79 required revisions, while scores below 0.70 led to deletion. The relevance and clarity assessment results for behavioral, intention, knowledge, norm, and attitude to use toilet questions yielded a scale CVI of more than 0.80, indicating that all items were valid and reliable. However, the habits, abilities, and self-regulation variables had varying I-CVI scores, indicating a need to revise or remove certain items. A culturally adapted and validated RANAS-based instrument is reliable for measuring latrine use behavior in Indonesia.